Overeducation among Swiss university graduates: determinants and consequences - Andrea Diem; Stefan C. Wolter (Journal for Labour Market Research, 2014)
This study uses the Swiss Graduate Survey data to investigate the determinants of job-education mismatch and the associated consequences on earnings while controlling for various ability and motivation factors, as well as socio-demographic, labor market and institutional characteristics. The results indicate that the likelihood of a job-education mismatch is significantly influenced by individual performance factors, such as final grades and study duration, and that the phenomenon affects approximately 15 % of university graduates. The study also shows that more than one-quarter of the individuals with a job-education mismatch 1 year after graduation are still working in a job that does not require a university degree 4 years later. In monetary terms, job-education mismatch is associated with a yearly wage penalty of approximately 4 - 10 % in the short to medium term.
Keywords: I21; J24; J31; 330; Hochschulabsolventen; unterwertige Beschäftigung; Berufseinmündung; Berufsverlauf; Lohnhöhe; Schweiz